Ludność wiejska na rynku pracy - Mossakowska, Ewa (Rural Population on Labour Market, 2006)
The paper consists of an analysis of changes in economic activity and certain socio-economic features of rural population over the period 2000-2004, as well as reasons of those changes. The study is based mainly on statistical data from the Labour Force Survey in Poland.During the considered period, the percentage of economically active and employed persons in rural areas decreased. At the same time, the rise in proportion of economically inactive persons and the unemployed was observed. Activity and employment rates are noted to be higher in a group of farm population rather than among rural population without agricultural holdings.Education level of rural population is low. Rural population often works in informal sector of the economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 143-148